A study on speech analysis in acquired maxillary defect patients treated with maxillary obturator - Purnendu Bhushan; Kavita Raj; Sadananda Hota; Debasish Mishra; Anjana Raut; Arun K Mohanty (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of the present study was to assess the speech analysis in acquired maxillary defect patients treated with maxillary obturator. Materials and Methods: Total of 16 patients were considered in the study. The age group of these patients ranged from 40 to 75 years with a mean age of 59.5 years, irrespective of their gender. The surgical obturator was fabricated using self-cure acrylic. The surgical obturator was delivered immediately after surgery. After a healing period of about 2 weeks, the surgical obturator was replaced by an interim prosthesis. This was processed with the help of heat-cure polymethylmethacrylate. The total number of patients was divided into two groups, namely, (A) Definitive obturator group and (B) Interim obturator group. The speech intelligibility (SI), was analyzed. Results: The mean scores for SI before prosthesis in definitive and interim groups were 19.13 ± 3.22 and 19.87 ± 1.72, respectively. This was increased after prosthesis insertion to 24.38 ± 1.30 and 22.37 ± 1.18, which further increased after adaptation period of 2 months to 28.75 ± 1.28 and 24.62 ± 1.59 in two groups. Conclusion: The present study concluded that speech was severely affected by maxillary resection and that rehabilitation with maxillary obturator was successful in restoring these aspects of speech.